1985
DOI: 10.1016/s0022-5347(17)47185-0
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacological Study of Alpha Adrenergic Receptor Subtypes in Smooth Muscle of Human Urinary Bladder Base and Prostatic Urethra

Abstract: Postsynaptic alpha adrenergic receptor subtypes mediating contraction of human urinary bladder base and prostatic urethra were investigated in vitro. Alpha adrenergic receptor agonists, noradrenaline and phenylephrine, induced contraction dose-dependently in these tissues. Alpha adrenergic receptor antagonists, prazosin and yohimbine, competitively antagonized the contraction induced by these agonists in the bladder base as well as prostatic urethra. The mean pA2 values for the antagonists in the bladder base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(44 citation statements)
references
References 10 publications
3
40
0
1
Order By: Relevance
“…Since Caine et al reported the therapeutic ef®cacy of phenoxybenzamine in BPH [6], a-adrenoceptor antagonists of three different types have been used to treat this condition. These are the ®rst-generation, nonselective a1/a2-antagonists (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Caine et al reported the therapeutic ef®cacy of phenoxybenzamine in BPH [6], a-adrenoceptor antagonists of three different types have been used to treat this condition. These are the ®rst-generation, nonselective a1/a2-antagonists (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most patients with BPH reportedly choose less aggressive interventions than TURP, although more aggressive than watchful waiting [2]. Recently, several investigations have signi®cantly more a1-adrenergic receptors in hypertrophic prostatic tissue than in normal tissue [3±5] and that blocking urethral a1-adrenoceptors causes the prostatic urethra to relax [6]. First-generation, nonselective a1/a2-antagonists, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As alpha-1 adrenoceptors were more predominant than alpha-2 adrenoceptors in male rabbits, they were used in this study. A study involving isometric contraction of isolated muscle strips of the human proximal urethra and prostate has revealed that alpha-1 adrenoceptors participate in contraction of the lower urinary tract in humans (Kunisawa et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The preference has been for longer acting and more uroselective a 1 -adrenoceptor antagonists [Brawer et al 1993]. Prazosin [Roehrborn et al 1995], terazosin [Chapple et al 1994], doxazosin [Jardin et al 1994], and alfuzosin [Kunisawa et al 1985], a 1 -adrenoreceptor antagonists have been used to treat BPH and increase urinary outflow and lessen symptoms. However, their use is associated with adverse effects that included dizziness, severe hypotension and dry mouth.…”
Section: Introductionmentioning
confidence: 99%